DIAGNOSTIC POSSIBILITIES OF 3D-COMPUTED TOMOGRAPHY WITH INTRALESIONAL APPLICATION OF CONTRAST MATERIAL IN A CASE OF VERY LARGE RADICULAR MAXILLARY CYST - A CASE REPORT - Galina Gavazova; Tanya Sbirkova; Dimitar L. Gospodinov (Peytchinski Publishing, 2017)
Introduction: Diagnosis of odontogenic cysts despite their benign nature is a critical and challenging problem. Aim: The aim of this article is to demonstrate a different diagnostic approach in case of very large odontogenic cyst. Materials and Methods: This study was executed on one male patient aged of 38 using 3D computed tomography and contrast material inside the lesion. Differential diagnosis made by the residents was compared to the histopathological examination as the gold standard for identifying the nature of the cysts. Results: This diagnostic approach using 3D computed tomography combined with contrast material injected inside the lesion shows the real borders of the cyst of the maxilla and helps oral surgeon in planning the volume of the surgical intervention. Conclusion: Precise diagnose ensure the possibility of doing the optimal surgical intervention- a precondition for best wound healing.